Leading with CARE how women around the world are inspiring businesses, empowering communities, and creating opportunity - Cantando, Mary (Jossey-Bass, 2009)
"In Leading with Care, management expert Mary Cantando examines the stories of trailblazing women in the developing world who, with help from the nonprofit organization CARE, have capitalized on personal and professional opportunities on the road to establishing self-sufficiency. As their stories reveal, through CARE, women around the world have overcome adversity co build new businesses, improve their health, prioritize education, and foster change in their communities."--BOOK JACKET